2017
DOI: 10.1167/iovs.17-21720
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Fibulin-3 Causes Proteoglycan Accumulation and Impaired Diffusion Across Bruch's Membrane

Abstract: PurposeThe mutation R345W in EFEMP1 (fibulin-3) causes macular degeneration. This study sought to determine whether proteoglycan content and diffusion across Bruch's membrane are altered in Efemp1ki/ki mice carrying this mutation or in Efemp1−/− mice.MethodsProteoglycans in mouse Bruch's membranes were stained with Cupromeronic Blue (CB). Heparan sulfated proteoglycan (HSPG) and chondroitin/dermatan sulfate proteoglycan (C/DSPG) distributions were visualized following treatments with chondroitinase ABC (C-ABC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Causal network analysis in the latter study highlighted common interaction between these two proteins with TIMP3; WT1 is thought to activate TIMP-3, which Fibulin-3 binds in turn to potentially amplify its inhibitory activity on proteolytic ECM enzymes. This function is further supported by studies of p.Arg345Trp EFEMP1 knockin mice which exhibited inhibited proteoglycenase (MMPs) activity in Bruch's membrane, the potential root of deposit formation located underneath the RPE (Zayas-Santiago et al, 2017). The retention of components in aberrant ECM is thought to elicit a complement system response which exacerbates deposit formation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Causal network analysis in the latter study highlighted common interaction between these two proteins with TIMP3; WT1 is thought to activate TIMP-3, which Fibulin-3 binds in turn to potentially amplify its inhibitory activity on proteolytic ECM enzymes. This function is further supported by studies of p.Arg345Trp EFEMP1 knockin mice which exhibited inhibited proteoglycenase (MMPs) activity in Bruch's membrane, the potential root of deposit formation located underneath the RPE (Zayas-Santiago et al, 2017). The retention of components in aberrant ECM is thought to elicit a complement system response which exacerbates deposit formation.…”
Section: Discussionmentioning
confidence: 90%
“…Eye-related features reported in the patients in this study included ptosis and myopia with no evidence of drusen formation or macular degeneration. Mouse models exhibiting the EFEMP1 p.(Arg345Trp) mutation developed sub-retinal pigment epithelium (RPE) deposits and presented with cardinal features of Malattia Leventinese and age-related macular dystrophy (Stanton et al, 2017;Marmorstein et al, 2007), whereas knockout (EFEMP1 −/− ) mice lacked these deposits and were resistant to its formation under induced conditions (Zayas-Santiago et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of mutant Hmcn1 and Hmcn2 knock-in mouse models or the transgenic overexpression of mutant Hmcn1 and Hmcn2 variants may allow to test whether such dominant negative effects of mutant Hemicentins may phenocopy Fraser syndrome-like features in mice. Such experiments would also allow to investigate a potential impact of Hmcn1 or Hmcn2 deficiency on the network formation of short fibulins in tissues, which, when disrupted, were shown to result in deficient elastic fiber formation with severe connective tissue consequences such as syndactyly, contractures, cutis laxa, aortic aneurysm formation and dissection [18,[23][24][25]. Strikingly, however, our ultrastructural analysis also revealed a requirement of wild-type Hmcn1 per se for proper BM integrity at the DEJ and MTJ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Significant elevations in MMP-9 mRNA, protein levels, and enzymatic activity were also observed in the brain following a variety of stimuli [ 33 , 34 ]. Studies on MMP-9 activation following learning in different behavioral tasks which all rely on activity in the hippocampus, such as the Morris water maze, inhibitory avoidance, contextual fear conditioning, object exploration, and response habituation, have demonstrated increases in the expression of pro and/or active forms of MMP-9 in the hippocampus [ 35 , 36 ]. In line with these previous studies, as shown by our study, repeated application of propofol on neonatal rat pups caused the deficit in cognitive functions, which was proved by impairment of spatial memory via the MWM test accompanied with increased expression of MMP-9 in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%